2016
DOI: 10.1177/1079063214558941
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Risk Factors for Sibling Incest

Abstract: Retrospective data from 1,821 women and 1,064 men with one or more siblings, provided anonymously using a computer-assisted self-interview, were used to identify risk factors for sibling incest (SI); 137 were participants in SI. In order of decreasing predictive power, the risk factors identified by the multiple logistic regression analysis included ever having shared a bed for sleeping with a sibling, parent-child incest (PCI), family nudity, low levels of maternal affection, and ever having shared a tub bath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Nevertheless, some studies address a number of specific factors that contribute to the emergence and maintenance of SSA. These include characteristics that promote sexual intimacy or contact (e.g., sharing the same bathtub or bed or nudity of parents and children), other types of incest within the family (such as father–daughter incest; Griffee et al, 2014), and situations where siblings turn to one another for affection, as in families that lack parental guidance and emotional presence (Ballantine, 2012; Brennan, 2006; Canavan et al, 1992; Griffee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, some studies address a number of specific factors that contribute to the emergence and maintenance of SSA. These include characteristics that promote sexual intimacy or contact (e.g., sharing the same bathtub or bed or nudity of parents and children), other types of incest within the family (such as father–daughter incest; Griffee et al, 2014), and situations where siblings turn to one another for affection, as in families that lack parental guidance and emotional presence (Ballantine, 2012; Brennan, 2006; Canavan et al, 1992; Griffee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The various definitions of SSA are a reflection of social attitudes (Krienert & Walsh, 2011). Accordingly, when SSA cases are reported to authorities, the tendency is to make two clear stereotypical assumptions: distinguish between a perpetrator and a victim sibling (Griffee et al, 2014), and presume that sexual abuse is necessarily traumatic and that the treatment should be focused on the trauma of the abuse. Both of these preconceptions are challenged by the routine relationship type found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the twin studies can just as easily be attributed to the conditioning effect of same sex incest as they can be attributed to a genetics cause because of the strong effect of same-sex incest among siblings on their adult sexual orientations irrespective of whether or not they are twins (See Beard et al, 2015, for further details). Griffee et al (2016) found that sharing a bed for sleeping and sharing tub baths with a sibling were both risk factors for sibling-incest, implying that the incidence of sibling incest would be increased in populations (such as twins) with increased incidences of sharing beds for sleeping or sharing tub baths. Computerized searches of internet posts and literature available through Medline in April, 2018 found that incidental data showing a high rate of twins sharing beds and tub baths were available in studies and internet posts having nothing to do with sexual orientation or incest.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…On the other hand, some studies have suggested that family nudity and sexuality are risk factors for sexual abuse, particularly incest. In a study on potential risk factors for sibling incest, Griffee et al (2016) found that family nudity behaviors correlated with a higher likelihood of sibling incest. Sibling incest in this study was widely defined as “any kind of sexual behavior between siblings (even showing and looking at genitals)” (p. 626).…”
Section: Literature Reviewmentioning
confidence: 99%